Genetic Doping and Health Damages - AA Fallahi Fallahi; AA Ravasi Ravasi; DD Farhud Farhud (Tehran University of Medical Sciences, 2011)
"nBackground: Use of genetic doping or gene transfer technology will be the newest and the lethal method of doping in future and have some unpleasant consequences for sports, athletes, and outcomes of competitions. The World Anti-Doping Agency (WADA) defines genetic doping as "the non-therapeutic use of genes, genetic elements, and/or cells that have the capacity to enhance athletic performance". The purpose of this review is to consider genetic doping, health damages and risks of new genes if delivered in athletes."nMethods: This review, which is carried out by reviewing relevant publications, is primarily based on the journals available in GOOGLE, ELSEVIER, PUBMED in fields of genetic technology, and health using a combination of keywords (e.g., genetic doping, genes, exercise, performance, athletes) until July 2010."nConclusion: There are several genes related to sport performance and if they are used, they will have health risks and sever damages such as cancer, autoimmunization, and heart attack.